2010
DOI: 10.1007/s00216-010-3735-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of functional changes in nanoparticle-exposed neuroendocrine cells with amperometry: exploring the generalizability of nanoparticle-vesicle matrix interactions

Abstract: Using two of the most commonly synthesized noble metal nanoparticle preparations, citrate-reduced Au and Ag, the impacts of short-term accidental nanoparticle exposure are examined in primary culture murine adrenal medullary chromaffin cells. Transmission electron microscopy (TEM), inductively coupled plasma atomic emission spectroscopy (ICP-AES) and Alamar Blue viability studies revealed that nanoparticles are taken up by cells but do not decrease cell viability within 48 hours of exposure. Carbon-fiber micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 41 publications
4
36
1
Order By: Relevance
“…Carbon-fiber microelectrode amperometry examination of exocytosis in nanoparticle-exposed cells revealed that nanoparticle exposure lead to decreased secretion of chemical messenger molecules, of up to 32.5% at 48 h of gold nanoparticle exposure. Repeated stimulation of exocytosis demonstrated that these effects persisted during subsequent stimulations, meaning that nanoparticles do not interfere directly with the vesicle recycling machinery but also that cellular function is unable to recover following vesicle content expulsion [118]. Similar results were also observed in mast cells [118].…”
Section: The Signalling Concept: Interaction Of Nanoparticles With Mamentioning
confidence: 61%
See 2 more Smart Citations
“…Carbon-fiber microelectrode amperometry examination of exocytosis in nanoparticle-exposed cells revealed that nanoparticle exposure lead to decreased secretion of chemical messenger molecules, of up to 32.5% at 48 h of gold nanoparticle exposure. Repeated stimulation of exocytosis demonstrated that these effects persisted during subsequent stimulations, meaning that nanoparticles do not interfere directly with the vesicle recycling machinery but also that cellular function is unable to recover following vesicle content expulsion [118]. Similar results were also observed in mast cells [118].…”
Section: The Signalling Concept: Interaction Of Nanoparticles With Mamentioning
confidence: 61%
“…Repeated stimulation of exocytosis demonstrated that these effects persisted during subsequent stimulations, meaning that nanoparticles do not interfere directly with the vesicle recycling machinery but also that cellular function is unable to recover following vesicle content expulsion [118]. Similar results were also observed in mast cells [118].…”
Section: The Signalling Concept: Interaction Of Nanoparticles With Mamentioning
confidence: 61%
See 1 more Smart Citation
“…(b) AFM is used to measure the adhesion force and stiffness of the cell membrane upon diesel NP exposure on human aortic endothelial cells [70]. (c) Carbon fiber microelectrode is a very sensitive technique with very high temporal resolution and has been used recently to identify the change in exocytosis behavior of endocrine or immune cells upon NP exposure [72][73][74].…”
Section: Atomic Force Microscopymentioning
confidence: 99%
“…The effect on cell viability when NP exposure was extended for 48 and 72 hours [74] was also studied. The effect of citrate reduced noble NPs, Au (28 nm) and Ag (61 nm), on neuroendocrine cells has been evaluated by Love and Haynes [72]. In this work, the uptake quantifications were measured using inductively coupled plasma-atomic emission spectroscopy (ICP-AES).…”
Section: Carbon Fiber Microelectrodementioning
confidence: 99%